RELATIONSHIP BETWEEN THE CATCH FISH WITH CONCENTRATION OF CHLOROPHYLL-a IMAGE DATA BASED ON MODIS AQUA IN WATERS NORTH OF JAVA - Nancy Sabella Nabasa Sirait; Usman '; Pareng Rengi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The purpose of this study was to determine the variability of Catch Per Unit Effort (CPUE) and chlorophyll-a and see the connection between the catch squid and chlorophyll-a concentrations found in the waters north of the island of Java in 2016. The data used is satellite image data Aqua MODIS Level 3 and using Quantum GIS applications 2.18. The analysis uses spatial analysis to see the variability of chlorophyll-a and CPUE while the analysis of the relationship between CPUE and chlorophyll-a simple linear regression. The results of the spatial analysis of data Aqua MODIS Level 3 has the highest maximum value is 63.443 mg / m³ in May with a minimum value is 0.070 mg / m³ and the average value is 1.160 mg / m³. From the results of linear regression analysis has a value of r is 0,4483 so that the effect of the concentration of chlorophyll-a to fluctuations in CPUE amounted to 20,1%.Keywords: Spatial Analysis, Aqua MODIS, Chlorophyll-a, and correlation of coefficient (r).